PEMBELAJARAN IPA BERBASIS EKSPERIMEN SEBAGAI UPAYA PENGEMBANGAN SIKAP ILMIAH SISWA SEKOLAH DASAR (KETELITIAN, KEJUJURAN, DAN DISIPLIN) - Marheni rayung Puspaningrum (STKIP Subang, 2026)
This study examines the effectiveness of experiment-based science learning in fostering scientific attitudes—accuracy, honesty, and discipline—among elementary school students. The problem addressed is the limited implementation of experimental learning in primary schools, where science instruction tends to be teacher-centered and focused mainly on concepts. The purpose of this research is to investigate how students’ scientific attitudes develop through direct participation in experimental activities. A descriptive qualitative approach using Classroom Action Research (CAR) was conducted with thirty-two fifth-grade students across two learning cycles that included planning, conducting, observing, analyzing, and reflecting on simple science experiments. Data were collected through observations, attitude rating scales, interviews, and documentation, and analyzed using an interactive qualitative analysis model. The findings reveal notable improvements in all indicators of scientific attitude, with N-Gain scores of 0.35 for accuracy, 0.34 for honesty, and 0.34 for discipline, all categorized as moderate effectiveness. Students showed increased precision in data recording, greater honesty in reporting results, and enhanced discipline in following scientific procedures. The study concludes that experiment-based science learning is effective in strengthening both scientific understanding and scientific character, making it highly relevant for primary science education.